2015
DOI: 10.1080/02723638.2015.1012363
|View full text |Cite
|
Sign up to set email alerts
|

The “Soviet” factor: exploring perceived housing inequalities in a midsized city in the Donbas, Ukraine

Abstract: In this paper, I revisit the role of Soviet legacy factors in explaining today's housing inequalities in a midsized post-Soviet city by investigating social, demographic, economic and geographic determinants of perceived housing quality. Building on a sample survey dataset (n = 3,000) that brings together both Soviet legacy effects and more universal influences on housing inequality, it is shown that various aspects of Soviet housing policy can be traced as well-preserved legacies today. The survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The increase in residence-based segregation may be affected by the change in the political system from a Soviet-era housing allocation system to the free market economy of the re-independent Estonia. Many studies have shown that because the Soviet Union's centrally allocating housing system tried to offer equal opportunities to all societal segments, segregation in Eastern Block cities generally was lower (Kährik and Tammaru 2010;Gentile 2015). Due to the collapse of the Soviet Union and the transition to a free housing market, an active stratification began: people started to become concentrated in different types of housing based on their income, nationality, and other social factors.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in residence-based segregation may be affected by the change in the political system from a Soviet-era housing allocation system to the free market economy of the re-independent Estonia. Many studies have shown that because the Soviet Union's centrally allocating housing system tried to offer equal opportunities to all societal segments, segregation in Eastern Block cities generally was lower (Kährik and Tammaru 2010;Gentile 2015). Due to the collapse of the Soviet Union and the transition to a free housing market, an active stratification began: people started to become concentrated in different types of housing based on their income, nationality, and other social factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one's income could have deteriorated as a result of warfare, so we do not include income as one of the matching criteria. Importantly, geographic segregation based on income is much less present in post-Soviet cities than in the west; the main socio-economic division of post-Soviet cities is between the residents of apartment buildings (majority) and those living in the older detached housing sector (Gentile, 2004(Gentile, , 2015. Based on the anecdotal evidence we collected from the battle of Slovyansk (in the Online appendix), DNR rebels used both types of housing for cover and the government also shelled both types of housing.…”
Section: Empirical Strategymentioning
confidence: 99%
“…This study clearly shows that public housing residualization is a path-dependent process, and its effects are context-specific. But our analysis, like many previous studies (Gentile, 2015;Gentile & Marcińczak, 2014;Hess et al, 2012), is limited to only one case. Consequently, assuming that cities differ not only in morphology, functional specialization, and exposure to globalization, but also in housing policies adopted and approaches to public housing, we suggest that future studies should investigate the process of public housing residualization in the comparative perspective encompassing a larger number of cities, preferably from different housing systems (Stephens et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, we believe that some general trends in the evolving socio-demographic composition of public housing residents can be distinguished. In trying to select a set of explanatory variables, we isolate the demographic, economic and social characteristics that appear to be significant predictors of housing segmentation and/or housing inequalities under socialism (Kulu, 2003;Szelenyi, 1983), under the post-socialist transition (and after; see Gentile, 2015;Gentile & Marcińczak, 2014;Hess et al, 2012;Soaita & Dewilde, 2020;Lux et al, 2011), and in Western Europe (Musterd, 2014;Norris & Winston, 2012). Accordingly, we select the following characteristics of household heads and their households from the national censuses: age, household type, level of educational attainment, and socio-professional category (for 2002 only).…”
Section: Methodsmentioning
confidence: 99%